2019
DOI: 10.1186/s40337-019-0265-z
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating attitudes correlate with body dissatisfaction among Kuwaiti male college students

Abstract: BackgroundThe prevalence of disordered eating attitudes and body dissatisfaction based on muscularity and body fat was investigated among male college students in Kuwait with a range of body mass index values including underweight, normal weight, overweight, and obese participants.MethodsData were collected, using the Eating Attitudes Test (EAT-26) and the Bodybuilder Image Grid (BIG), from 400 male undergraduate students (84.8% Kuwaiti nationals) recruited from both public and private universities in Kuwait. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 64 publications
(83 reference statements)
1
22
0
7
Order By: Relevance
“…[ 6 8 16 ] Moreover, rapid advancement in life and the influence on beauty standards in the Middle East by the social media could eventually affect beliefs and perception of the ideal body weight and body image of both genders. [ 11 16 ] In line with this explanation is the fact that more than half of the participants in the current study who were said to have been encouraged by social media influencers to go to the gym had higher scores in EAT-26. Moreover, the majority of participants who used social media to improve the diet and weight had problematic eating behaviors and needed referral to a mental health provider.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…[ 6 8 16 ] Moreover, rapid advancement in life and the influence on beauty standards in the Middle East by the social media could eventually affect beliefs and perception of the ideal body weight and body image of both genders. [ 11 16 ] In line with this explanation is the fact that more than half of the participants in the current study who were said to have been encouraged by social media influencers to go to the gym had higher scores in EAT-26. Moreover, the majority of participants who used social media to improve the diet and weight had problematic eating behaviors and needed referral to a mental health provider.…”
Section: Discussionsupporting
confidence: 60%
“…EAT-26 is a highly sensitive, reliable screening tool used in previous studies to assess eating disorder risks in students at high school or college, and athletes. [ 6 7 10 11 ] However, the EAT-26 alone does not provide a definite diagnosis of eating disorders and further clinical evaluation is crucial. [ 1 10 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body dissatisfaction is correlated to emotional eating (103) , eating attitude (104) , and binge eating (95) , while the insecure attachment is more known to be a risk factor for the emergence of disordered eating (39) . Binge eating was more related to the anxious attachment, while restrained eating was more related to the avoidant attachment (33) .…”
Section: Body Dissatisfactionmentioning
confidence: 99%
“…Consequently, people fail in their actions and show no reaction with the idea that they will see the same result in a similar case, and learned helplessness is experienced then (12). Ebrahim et al reported that the high prevalence of eating disorders among the participants of their study was related to the increase in their dissatisfaction with their body image in relation to their body fat and muscle ratios (13). Another relevant study indicated that the use of a weight loss program by people with obesity was not a selection criterion for the program, and the use of this program would increase with a decrease in the Body Mass Index (BMI) (9).…”
Section: Introductionmentioning
confidence: 98%